The Power Behind Cloud Adoption in Healthcare Digital Government - Mahalingam, Sheila (Journal of Emerging Technologies and Industrial Applications, 2024)
In recent years, Malaysia has witnessed a significant shift towards cloud adoption, driven by various factors including the need for greater efficiency, scalability, and cost-effectiveness in delivering public services. This paper provides an in-depth analysis of the key drivers, challenges, and opportunities associated with cloud adoption in Malaysia's digital government landscape. Drawing upon empirical research and case studies, it examines the strategic considerations guiding government agencies in their migration to cloud-based solutions. Furthermore, the paper discusses the potential benefits of cloud adoption, such as enhanced agility, improved service delivery, and increased innovation in public service provision. It also addresses concerns related to data security, privacy, and regulatory compliance, highlighting the importance of robust governance frameworks in mitigating risks associated with cloud deployment. Through a comprehensive review of current trends and best practices, this paper aims to shed light on the power behind cloud adoption in Malaysia's Healthcare digital government, offering valuable insights for policymakers, IT professionals, and stakeholders involved in the country's digital transformation journey. Top of Form .